A molecular phylogeny of the genus Drimia (Asparagaceae: Scilloideae: Urgineeae) in India inferred from non-coding chloroplast and nuclear ribosomal DNA sequences - Saha, Partha S. (Sci Rep, 2019)
The evolutionary history of the medicinally important bulbous geophyte Drimia (subfamily: Scilloideae) has long been considered as a matter of debate in the monocot systematics. In India the genus is represented by a species complex, however, the taxonomic delimitation among them is ill-defined till date. In the present study, a comprehensive phylogenetic relationship among Indian species of this genus has been inferred for the first time based on chloroplast DNA trnL intron, rps16-trnK intergenic spacer, atpB-rbcL intergenic spacer and ribosomal DNA ITS1-5.8S-ITS2 sequences, leaf morphology, anatomy, stomatal characteristics and pollen exine ornamentations. The present findings revealed the monophyletic origin of the Indian members of Drimia and grouped them into two possible lineages (clade- I and II). The phylogenetic tree based on cpDNA concatenated sequences further resolved the clade-I into two distinct subclades (I and II) and clarified the intraspecies relationship among the studied members. The present study suggested a strong relationship between the molecular phylogeny and the morphological characteristics of the species studied. A possible trend of evolution of two important traits: ‘type of palisade cells’ in leaf and ‘pollen exine patterns’ among the members of Drimia in India was also suggested.